Minimizing the Problems of Enterprise Resource Planning (ERP) Implementation for Small to Medium Cigarette Company Through Framework for Applications of Systems Thinking (FAST) - Muhammad Yasir Zain (Department of Informatics,Faculty of Industrial Technology,Islamic University of Indonesia, 2008)
This research is aimed to study the possibilities of implementing Enterprise Resource Planning (ERP) within Small to medium enterprises especially Cigarette Company through analysis, design systems and implementing phase. Since ERP system shows its power, lots of large company tried to implement ERP system within the company. In 2000, more than 60% of fortune 1000 companies were considering or had already implement at least one core of ERP module, even though it need huge capital to be invested. Lower scale of companies could not afford to implement the ERP system. The emerging Small to Medium Enterprise (SME) drove companies to more tight competition that force the companies to create more effective and efficient business process. Some of the companies tried to implement ERP systems through in-house development system. But they have to face failure since there are obstacles faced by the company such as less experience on developing systems. To fulfill the demand of ERP system, many vendors offer ready-to-use system for SME which sold in more affordable price or even free such as open source systems. The ready-to-use systems are quite easy to implement. Anyhow, problems might occur on the implementation process. FAST which stands for Framework for Application of Systems Thinking might help the company to reduce the problems that might occur on the implementation process since it has several steps as the problems filter.